Diversity and predictive metabolic pathways of the prokaryotic microbial community along a groundwater salinity gradient of the Pearl River Delta, China. Issue 1 (December 2018) - Sang, Shilei; Zhang, Xiaoying; Dai, Heng; Hu, Bill; Ou, Hao; Sun, Liwei
Abstract Almost half of the groundwater in the Pearl River Delta (PRD) contains salt water originally derived from paleo-seawater due to the Holocene transgression, which then generates intense physicochemical gradients in the mixing zone between freshwater and saltwater. Although some studies have been conducted on the hydrological and geochemical characteristics of groundwater in the PRD to monitor the intrusion of seawater, little attention has been paid to the microbial community of this particular region. In this study, we implemented a high-throughput sequencing analysis to characterize the microbial communities along a salinity gradient in the PRD aquifer, China. Our results indicated that the microbial community composition varied significantly depending on the salinity of the aquifer. The presence of abundant anaerobic microorganisms of the generaDesulfovibrio andMethanococcus in certain saltwater samples may be responsible for the gas generation of H2 S and CH4 in the stratum. In saline water samples (TDS > 10 g/L), the linear discriminant analysis effect size (LEfSe) analysis found two biomarkers that usually live in marine environments, and the aquifers of the PRD still contained large quantity of saltwater, indicating that the impact of the paleo-seawater has lasted to this day. The predictive metagenomic analysis revealed that the metabolic pathways present in the groundwater samples studied, included the degradation of pesticides and refractory organics (dichlorodiphenyltrichloroethane (DDT), atrazine and polycyclic aromatic hydrocarbons), matter cycling (methane, nitrogen and sulfur), and inorganic ion and mineral metabolites. This study can help enhance our understanding of the composition of the microbial assemblages and its implications as an environmental indicator in an aquifer affected by saltwater intrusion.